Prediction of structural and metal-to-semiconductor phase transitions in nanoscale MoS2, WS2, and other transition metal dichalcogenide zigzag ribbons - Güller, Francisco (2015)
While MoS2 and WS2 nanostructures gain an increasing importance in a number of recent technological applications, the control of their structure as a function of their size and their environment appears of prominent importance. In the present study which relies on first-principles simulations, we predict the dimerized 1T′ structural phase to be the actual ground state of MoS2, WS2, and MoSe2 zigzag nanoribbons of small width and monolayer thickness. We assign this result to the competition between edge energy - which favors the nonpolar 1T′ edges over the polar 1H edges - and the energy of atoms in the center of the ribbons - which favors the 1H ground state of the infinite monolayers. A metal-to-semiconductor transition accompanies the structural transition. At variance, ZrS2 zigzag ribbons are predicted to display the 1T structure whatever their width. In compounds of major technological importance, such structural and electronic flexibility associated with polarity effects opens the possibility for controlling the ribbon type during synthesis.